Purism in the German language during the nineteenth century, 1789-1889 - Kirkness, A; Kirkness, Alan C. (1966)
﻿ Even more novel to the English speaker than the fact that foreign words should represent a problem at all are the frequent, often concerted reactions against them in Germany from the seventeenth century on. These reactions - attempts to eliminate borrowed words and replace them with German expressions - have been relatively little studied and the references in histories of language usually apply to the baroque Sprachgesellschaften and one or two individual purists. No detailed general survey of German purism is available, there is no bibliography on the subject, and the contribution of the purists has not been fully assessed. This study is intended as a preliminary step towards meeting these needs and offers a critical, fully documented account of purism in the hundred years between 1789 and 1889. This period begins with J.H. Campe, the most important German purist, who was the first to approach the question systematically and in great detail, and ends with the Berlin Declaration of 1889 objecting to the policies of the newly founded Allgemeiner Deutscher Sprachverein. The Sprachverein has fully documented its own history and achievements, but for the rest only Campe and F.L. Jahn have been studied critically. I have sought to investigate who the purists were, how they approached language, why they considered purism necessary, what foreign words they rejected, how they tried to replace them, and to give an account of their activity. [See pdf. for rest of abstract.]